Voters’ reactions to the 2019 presidential debate in Nigeria (2021)
Over the years, debate scholarship has interrogated the usefulness or relevance of political debates in the electoral process. While there is an avalanche of debate effect studies in established democracies such as America, scant attention has been paid to presidential debates in Nigeria. Based on the Rational Choice theory and the Uses and Gratifications theory, this study therefore investigated voters’ response to the 2019 presidential debate in Nigeria. The study adopted the survey research design and administered questionnaire on 460 voters in Ekiti State, Nigeria. The respondents were selected using the multi-stage sampling technique. Findings revealed that although the 2019 presidential debate had very little influence on voters’ voting decisions in the 2019 presidential election, a majority of the voters perceived the presidential debate as relevant to the electoral process as it increased their knowledge of political issues as well as their knowledge of the candidates. Moreover, political affiliation was found to be the most significant factor that influenced voters’ choice of candidate. The study therefore recommended that political campaign managers and politicians should leverage the debate platform to promote their candidates but should not assume this would significantly influence voting decisions